2001
DOI: 10.1007/s001250100545
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric documentation of abnormal intramyocellular fat storage and reduced glycogen in obese patients with Type II diabetes

Abstract: This study shows that fat accumulates intramyocellulary while glycogen stores are simultaneously reduced in obese subjects with Type II (non-insulin-dependent) diabetes mellitus. Quantitatively, a major component of the excessive lipid accumulation could be secondary in origin, related to the diabetic state in itself, although a contribution from the altered insulin action cascade of obesity and diabetes cannot be excluded. In both groups significant positive relations were found between circulating and intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(10 citation statements)
references
References 33 publications
2
6
2
Order By: Relevance
“…We first showed that the patients with type 2 diabetes (and thus insulin resistance) had increased accumulation of lipid droplets in their skeletal muscle, in agreement with earlier results (1,17,18). There was very little lipid accumulation in biopsy samples from both lean healthy and obese nondiabetic control subjects, demonstrating that obese people do not necessarily store fat in their skeletal muscles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We first showed that the patients with type 2 diabetes (and thus insulin resistance) had increased accumulation of lipid droplets in their skeletal muscle, in agreement with earlier results (1,17,18). There was very little lipid accumulation in biopsy samples from both lean healthy and obese nondiabetic control subjects, demonstrating that obese people do not necessarily store fat in their skeletal muscles.…”
Section: Discussionsupporting
confidence: 91%
“…Insulin resistance plays a major role in the development of type 2 diabetes and is highly related to the accumulation of triglycerides in skeletal muscle (1,2). Triglycerides are stored in the cell in cytosolic lipid droplets, which consist of a core of neutral lipids surrounded by a monolayer of amphipathic lipids (3,4).…”
mentioning
confidence: 99%
“…In spite of their IR and reduced cardiovascular fitness, T1D youth showed paradoxically normal intramyocellular lipid content (IMCL). This finding contradicts the previously well- established theory that IMCL accumulation is a marker for insulin resistance in both T1D and T2D [39], [40].…”
Section: Discussioncontrasting
confidence: 99%
“…LD accumulation in skeletal muscle is closely linked to insulin resistance (e.g., Refs. 15,16,27,37), and recent studies suggest that an accumulation of LDs specifically in the subsarcolemmal location is detrimental for insulin sensitivity compared with LDs in the intermyofibrillar location (3, 9, 28, 35). However, the underlying mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%